Síntese de Pirimidinas derivadas de 7,7,7-trialo-4-metoxi-6-oxo-4- heptenoatos de metila e bi-heterociclos trifluormetilados - Malavolta, Juliana Limana (2012)
An efficient method to obtain pyrimidinones and pyrimidines trialomethylated from the cyclocondensation reaction of compounds of methyl 7,7,7-trihalo-4-methoxy-6-oxoheptenoate with urea and differents amidines providing the series of compounds pyrimidines and pyrimidinones trifluoromethylated and trichloromerthylated is reported.Some compounds of the series were selected and brought to reaction with hydrazine monohydrate obtaining the series of new 6-(trifluoromethyl)pyrimidin-4-propanehydrazide, of which two were later brought to reaction with a series of β-alkoxyvinyltrifluoromethyl ketones giving the new series of bis-heterocyclic 4-[(5-(trifluoromethyl)-5-hydroxy-4,5-dihydro-1H-pyrazol-1-yl)-1-propan-1-one-3-yl]-6- (trifluoromethyl)pyrimidine compounds. The structures of all synthesized compounds were confirmed by 1H and 13C NMR data, and two-dimensional NMR techniques like HETCOR and COLOC, ans mass spectrometry data.